(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
In the article is estimated climatic conditions influencing on productivity of cultivated cultures using in soil bonitiration and earth cadastre composition. It is given an account of determination of methodical approach of contribution of climatic factors on crop capacity, which will let us determine high borders of ecological optimum of cultivated agricultural cultures.